Cestodes of Pseudobatos horkelii (Müller and Henle) (Rhinopristiformes) including Rhinebothrium quequense n. sp. (Rhinebothriidea) and Caulobothrium pieroi n. sp. (“Tetraphyllidea”) from the southwestern Atlantic - Menoret, Adriana; Ivanov, Verónica A. (Zootaxa, 2023)
Two new species of cestodes were described from the Brazilian guitarfish, Pseudobatos horkelii (Müller and Henle) (Rhinopristiformes: Rhinobatidae), from coastal waters off Argentina in the southwestern Atlantic Ocean. Rhinebothrium quequense n. sp. (Rhinebothriidea) differs from its congeners by a combination of morphological characters, including the total number of loculi, the absence of loculi at the level of bothridial constriction, the number of testes per proglottid, and the number of proglottids per worm. Caulobothrium pieroi n. sp. (“Tetraphyllidea”) can be distinguished from the other members of the genus by the following set of morphological features including the presence of stalked bothridia with apical sucker, the number of loculi per bothridium, the number of testes per proglottid, and the number of proglottids per worm. The discovery of R. quequense n. sp. and C. pieroi n. sp. in the Brazilian guitarfish not only increases the number of rhinebothriideans and “tetraphyllideans” in the southwestern Atlantic, but also expands the elasmobranchs list to include P. horkelii for the first time as a new host record for cestodes globally. In addition, this is not only the first report of a species of Rhinebothrium in rhinobatids in the region, but it is also the first Caulobothrium species infecting a rhinopristiform batoid.